Aspectos biológicos de Cyclocephala verticalis burmeister (coleoptera: scarabaeidae) - Rodrigues,Sérgio R (2010)
Several coleopterans of the Scarabaeidae family (Pleurosticti) are reported as important pests of agricultural crops, but little information on their biology is available. We describe our observations on the biology of adult Cyclocephala verticalis Burmeister collected with light traps from January, 2006 to December, 2007, in Aquidauana, MS, Brasil. Field collected adults were taken to the laboratory and kept in plastic containers containing soil and seedlings of Brachiaria decumbens under controlled conditions (26 ± 1ºC with 12h of photophase). The embrionary period of C. verticalis took 17.2 days in the average. The duration of first-, second- and third-instar larvae was 22.0, 23.7 and 138.1 days in the average, respectively. The prepupal stage took 12.7 days and the pupal stage 14.8 days. Adults obtained in laboratory lived 37.5 days. The complete cycle reached 228.6 days, making possible the development of a single generation per year. In laboratory conditions, the copulation lasted about 19 min and 20 seconds. The adults fly in a great amount in September and October, being this the main period of oviposition in the field.